Efficacy of Regorafenib in Metastatic Colorectal Cancer: A Multi-institutional Retrospective Study - Aljubran, Ali (Clin Med Insights Oncol, 2019)
BACKGROUND: Regorafenib is a multi-kinase inhibitor approved for treatment of refractory advanced colorectal cancer. It was found in the clinical trials to have a modest benefit and significant toxicity. Our aim was to assess the outcome in our local clinic practice. PATIENTS AND METHODS: Records of patients with confirmed colorectal cancer treated with regorafenib were reviewed. Clinical, pathological, and molecular data were collected. Efficacy and factors of possible prognostic significance were analyzed. RESULTS: A total of 78 patients with metastatic colorectal cancer were treated with regorafenib from February 2014 to February 2016 in 4 different institutions (median age: 50.5 years; male: 40 [51.3%]; KRAS mutant: 41 [52%]; right colonic primary: 18 [23%]). A total of 52 patients (66.7%) had Eastern Cooperative Oncology Group (ECOG) Performance Status of 0 to 1, whereas in 25 patients (32.1%) it was >1. In total, 58 patients (74%) had dose reduction. No patient achieved objective response, 15 patients (19%) achieved stable disease, and 56 patients (72%) had progressive disease. With a median follow-up of 6.5 months, the median progression-free survival was 2.8 months (95% confidence interval [CI], 2.5-3.3) and overall survival was 8.0 months (95% CI, 6.2-9.7). Only performance status of ⩽1 had a statistically significant impact on progression-free survival and overall survival in both univariate and multivariate analyses. CONCLUSIONS: Regorafenib in our clinical practice has equal efficacy to reported data from pivotal registration trials. Our data suggest that performance status is the most important prognostic factor in patients treated with regorafenib, suggesting a careful selection of patients.